2010
DOI: 10.1166/jnn.2010.2185
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fouling Release Silicone/Carbon Nanotube Nanocomposite Coatings: On the Importance of the Nanotube Dispersion State

Abstract: The present work reports on the influence of the dispersion quality of multiwall carbon nanotubes (MWCNTs) in a silicone matrix on the marine fouling-release performance of the resulting nanocomposite coatings. A first set of coatings filled with different nanofiller contents was prepared by the dilution of a silicone/MWCNTs masterbatch within a hydrosilylation-curing polydimethylsiloxane resin. The fouling-release properties of the nanocomposite coatings were studied through laboratory assays with the marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…To obtain a fine dispersion of CNT in the PDMS matrix a masterbatch approach after Beigbeder et al (2010) was followed. Namely, a pre-dispersion of 0.5 wt% CNT in an addition-curing PDMS (BioCyl part A) was diluted with bis(silanol)-terminated PDMS and then mixed with block copolymer Sz6 and the condensation crosslinker ES40.…”
Section: Preparation Of Two-layer Coatingsmentioning
confidence: 99%
“…To obtain a fine dispersion of CNT in the PDMS matrix a masterbatch approach after Beigbeder et al (2010) was followed. Namely, a pre-dispersion of 0.5 wt% CNT in an addition-curing PDMS (BioCyl part A) was diluted with bis(silanol)-terminated PDMS and then mixed with block copolymer Sz6 and the condensation crosslinker ES40.…”
Section: Preparation Of Two-layer Coatingsmentioning
confidence: 99%
“…Although CNTs are recognized to be toxic, the matrix does not release CNT which is a significant feature in relation to any ecotoxilogical issues associated with CNTs. For further details of these coatings, the reader can refer to Beigbeder et al (2008aBeigbeder et al ( , b, 2009Beigbeder et al ( , 2010. In order to support the experiments, one more coating and two different uncoated surfaces were included in the measurements as reference.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Meanwhile, the speed of biomass accumulation for each coating was also different in the first two weeks. It seemed that PDMS (12) and PDMS (26) had the largest accumulation speed, but three other coatings (PDMS (29), PDMS (32) and PDMS (58), accumulated more biomass in the first three days. These observations suggested that the compositional change and its dynamics in the tested biofilms were modulated by the nano-fillers.…”
Section: Biomass Determinationmentioning
confidence: 99%
“…could reach 99.9% and 99.8% in 60 min, respectively. Beigbeder A et al [12] found slight addition of multiwall carbon nanotubes in a silicone matrix can dramatically increase the ability to hinder marine alga Ulva and barnacle. Chen TY et al [13] found that addition of silicone oil in a low surface energy coating leads to apparent less attachment of barnacle larvae but little effect on algae's attachment.…”
Section: Introductionmentioning
confidence: 99%